Economic growth, urbanization and social inequality: Reflections on the conservative Modernization - Pires, Marcos Cordeiro [UNESP] (2013)
China is now facing a sudden change of redistribution of population in space as her urban population exceeds rural population. It seems necessary to learn others’ lessons by analyzing the urbanization of other developing countries, especially Brazil’s. To an extent, Brazil and some other developing countries have been unsuccessful in coordination for urbanization and improving living quality. The megacities in Latin America are the examples of swollen cities, and large groups excluded from the system of public services. It reflects in both short of infrastructures in many areas and high-levels of violence unique in the big cities in Latin America. Then the author summarizes Brazil’s lessons. Firstly, he describes the determinants in Brazil’s urbanization, especially the industrialization between 1930 and 1980. Secondly, the incentives for internal migration are analyzed, especially the industrial centralization in the southeast and the recessions in other areas. Finally, the characteristics of the present round of absorption of labor and the roots for the severe social inequality are discussed.